Functional diversity of the above-ground fungal community under long-term integrated, organic and biodynamic Vineyard Management - Katharina Steng; Friederike Roy; Harald Kellner; Julia Moll; Susanne Tittmann; Johanna Frotscher; Johanna Döring (Environmental Microbiome)
Abstract Background Sustainable agriculture increasingly emphasizes the importance of microbial communities in influencing plant health and productivity. In viticulture, understanding the impact of management practices on fungal communities is critical, given their role in disease dynamics, grape and wine quality. This study investigates the effects of integrated, organic, and biodynamic management practices on the diversity and function of fungal communities in a vineyard located in Geisenheim, Germany, focusing on above-ground parts such as bark, leaves, and grapes. Results Our findings indicate that while overall fungal species richness did not significantly differ among management systems across various compartments, the composition of these communities was distinctly influenced by the type of management system. In particular, leaf and grape compartments showed notable variations in fungal community structure between integrated and organic/biodynamic management. No differences were observed between organic and biodynamic management. Integrated management demonstrated a significantly higher abundance of mycoparasites in comparison to organic and biodynamic management, primarily attributed to the increased presence of Sporobolomyces roseus, Sporobolomyces ellipsoideus and Rhodotorula glutinis. Conclusions The findings highlight the importance of management practices in shaping fungal community composition and function in vineyards. Although overall species richness remained unaffected, community composition and functional diversity varied, highlighting the potential for strategic microbiome management to enhance vineyard sustainability and plant health.